Neuroembryology. (1st December 2016) - Darnell, Diana; Gilbert, Scott F.
Abstract : How is it that some cells become neurons? And how is it that neurons become organized in the spinal cord and brain to allow us to walk and talk, to see, recall events in our lives, feel pain, keep our balance, and think? The cells that are specified to form the brain and spinal cord are originally located on the outside surface of the embryo. They loop inward to form the neural tube in a process called neurulation. Structures that are nearby send signals to the posterior neural tube to form and pattern the spinal cord so that the dorsal side receives sensory input and the ventral side sends motor signals from neurons to muscles. In the brain, stem cells near the center of the neural tube migrate out to form a mantel zone, and a set of dividing cells from the mantle zone migrate further to produce a second set of neurons at the outer surface of the brain. These neurons will form the cerebral cortex, which contains six discrete layers. Each layer has different connections and different functions. WIREs Dev Biol 2017, 6:e215. doi: 10.1002/wdev.215 This article is categorized under: Early Embryonic Development > Gastrulation and Neurulation Early Embryonic Development > Development to the Basic Body Plan